Genome-wide Analyses Identify a Novel Risk Locus for Nonsyndromic Cleft Palate. (December 2020) - He, M.; Zuo, X.; Liu, H.; Wang, W.; Zhang, Y.; Fu, Y.; Zhen, Q.; Yu, Y.; Pan, Y.; Qin, C.; Li, B.; Yang, R.; et al.
The 3 major subphenotypes observed in patients with nonsyndromic orofacial clefts (NSOFCs) are nonsyndromic cleft lip only (NSCLO), nonsyndromic cleft lip with palate (NSCLP), and nonsyndromic cleft palate only (NSCPO). However, the genetic architecture underlying NSCPO is largely unknown. Here we performed a 2-stage genome-wide association study (GWAS) on NSCPO and replication analyses of selected variants in other NSOFCs from the Chinese Han population. We identified a novel locus (15q24.3) and a known locus (1q32.2) where variants in or near the gene reached genome-wide significance (2.80 × 10 −13 < P < 1.72 × 10 −08 ) in a test for association with NSCPO in a case-control design. Although a variant from 15q24.3 was found to be significantly associated with both NSCPO and NSCLP, the direction of estimated effects on risk were opposite. Our functional annotation of the risk alleles within 15q24.3 coupled with previously established roles of the candidate genes within identified risk loci in periderm development, embryonic patterning, and/or regulation of cellular processes supports their involvement in palate development and the pathogenesis of cleft palate. Our study advances the understanding of the genetic basis of NSOFCs and provides novel insights into the pathogenesis of NSCPO.